Aspirin as an adjuvant treatment for cancer: feasibility results from the Add-Aspirin randomised trial. (November 2019) - Joharatnam-Hogan, Nalinie; Cafferty, Fay; Hubner, Richard; Swinson, Daniel; Sothi, Sharmila; Gupta, Kamalnayan; Falk, Stephen; Patel, Kinnari; Warner, Nicola; Kunene, Victoria; Rowley, Sam; Khabra, Komel; et al.
Summary: Background: Preclinical, epidemiological, and randomised data indicate that aspirin might prevent tumour development and metastasis, leading to reduced cancer mortality, particularly for gastro-oesophageal and colorectal cancer. Randomised trials evaluating aspirin use after primary radical therapy are ongoing. We present the pre-planned feasibility analysis of the run-in phase of the Add-Aspirin trial to address concerns about toxicity, particularly bleeding after radical treatment for gastro-oesophageal cancer. Methods: The Add-Aspirin protocol includes four phase 3 randomised controlled trials evaluating the effect of daily aspirin on recurrence and survival after radical cancer therapy in four tumour cohorts: gastro-oesophageal, colorectal, breast, and prostate cancer. An open-label run-in phase (aspirin 100 mg daily for 8 weeks) precedes double-blind randomisation (for participants aged under 75 years, aspirin 300 mg, aspirin 100 mg, or matched placebo in a 1:1:1 ratio; for patients aged 75 years or older, aspirin 100 mg or matched placebo in a 2:1 ratio). A preplanned analysis of feasibility, including recruitment rate, adherence, and toxicity was performed. The trial is registered with the International Standard Randomised Controlled Trials Number registry (ISRCTN74358648) and remains open to recruitment. Findings: After 2 years of recruitment (October, 2015, to October, 2017), 3494 participants were registered (115 in the gastro-oesophageal cancer cohort, 950 in the colorectal cancer cohort, 1675 in the breast cancer cohort, and 754 in the prostate cancer cohort); 2719 (85%) of 3194 participants who had finished the run-in period proceeded to randomisation, with rates consistent across tumour cohorts. End of run-in data were available for 2253 patients; 2148 (95%) of the participants took six or seven tablets per week. 11 (0·5%) of the 2253 participants reported grade 3 toxicity during the run-in period, with no upper gastrointestinal bleeding (any grade) in the gastro-oesophageal cancer cohort. The most frequent grade 1–2 toxicity overall was dyspepsia (246 [11%] of 2253 participants). Interpretation: Aspirin is well-tolerated after radical cancer therapy. Toxicity has been low and there is no evidence of a difference in adherence, acceptance of randomisation, or toxicity between the different cancer cohorts. Trial recruitment continues to determine whether aspirin could offer a potential low cost and well tolerated therapy to improve cancer outcomes. Funding: Cancer Research UK, The National Institute for Health Research Health Technology Assessment Programme, The MRC Clinical Trials Unit at UCL.